Potential of Media Impact to the Formation of Students Tolerance - Svitlana Yakimenko (Pedagogical Discourse, 2013)
In this article the author considers the social and educational opportunities of impact the media to formation of students tolerance and ideological positions. The author considers mass media as element of socialization of young people. Both positive and negative television possibilities to consider possibilities of involving television to upbringing and education the formation of ideology of the young man are analyzed in the article.